Gain-of-Function STAT1 Mutation With Familial Lymphadenopathy and Hodgkin Lymphoma - Henrickson, Sarah E.; Dolan, Joseph G.; Forbes, Lisa R.; Vargas-Hernández, Alexander; Nishimura, Shiho; Okada, Satoshi; Kersun, Leslie S.; Brodeur, Garrett M.; Heimall, Jennifer R. (Frontiers in Pediatrics, 2019)
We describe a novel T437N STAT1 mutation that we demonstrate yields gain-of-function (GOF) found in the mother and 3 of her 4 children. All of the 4 patients with the T437N GOF STAT1 mutation experienced lymphadenopathy. However, 2 of the children developed Nodular Lymphocyte Predominant Hodgkin Lymphoma (NHLPL) and have responded to chemotherapeutic regimens. The fourth sibling has neither the STAT1 variant nor lymphadenopathy or malignancy. To our knowledge this is the first description of a potential association between STAT1 GOF mutations and lymphoma development.